Influence of timing of endectocidic antiparasitic treatment on its efficacy in overwintering reindeer - Oksanen, A. (Rangifer, 1996)
To find out if timing of endectocidic antiparasitic treatment is critical for its efficacy in overwintering reindeer, 72 hinds of the Kaamanen Experimental Reindeer Herd were randomly allocated to four groups. Three groups received ivermecrin mixture orally once at a dose of 200 pg/kg, either in September, December, or February, and one group was left untreated. Antiparasitic efficacy was evaluated by counting Hypoderma tarandi and Cephenemyia trompe larvae in April, and by faecal examinanon for trichostrongylid nematode eggs in March and April. Production efficacy consequences were assessed by comparing animal weight development from November to April, and calf birth weights. No difference could be seen in the antiparasitic efficacy of the treatments; all were 100 % efficient against H. tarandi larvae (warbles) and C. trompe larvae (throat bors), and reduced the trichostrongylid egg output by 62 to 74%. Weight gains of the groups were not significantly different, however the calf birrh weights differed nearly significantly (P = 0.057). On average, smallest calves were produced by the untreated group.